2017
DOI: 10.1016/j.bbrc.2017.09.098
|View full text |Cite
|
Sign up to set email alerts
|

High glucose derived endothelial microparticles increase active caspase-3 and reduce microRNA-Let-7a expression in endothelial cells

Abstract: The experimental aim of this study was to determine the effects of high glucose-induced endothelial microparticles (EMPs) on endothelial cell susceptibility to apoptosis. Human umbilical vein endothelial cells (HUVECs) were cultured (3rd passage) and plated in 6-well plates at a density of 5.0 × 105 cells/condition. Cells were incubated with media containing 25mM D-glucose (concentration representing a diabetic glycemic state) or 5mM D-glucose (normoglycemic condition) for 48 h to generate EMPs. EMP identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Chettab et al have shown that the expression of ICAM-1 as well as the production of IL-8, are significantly increased in HUVECs cultured in HG medium compared to cells cultured in normal glucose (NG, 5.5 mM) conditions (52). Bammert et al found out that incubation of HUVECs with HG media promotes the generation of endothelial microparticles (EMPs) that, when added to normally cultured HUVECs, downregulate the expression of anti-apoptotic microRNA miR-Let7a, but enhance the synthesis of active caspase-3 and cause cell apoptosis (53). Several microRNAs, including miR-21, miR-26a, miR-30, miR-92a, miR-126, miR-139, miR-199a, miR-222, and miR-let7d, regulate vascular homeostasis.…”
Section: Effects Of T2dm On the Circulatory Systemmentioning
confidence: 99%
“…Chettab et al have shown that the expression of ICAM-1 as well as the production of IL-8, are significantly increased in HUVECs cultured in HG medium compared to cells cultured in normal glucose (NG, 5.5 mM) conditions (52). Bammert et al found out that incubation of HUVECs with HG media promotes the generation of endothelial microparticles (EMPs) that, when added to normally cultured HUVECs, downregulate the expression of anti-apoptotic microRNA miR-Let7a, but enhance the synthesis of active caspase-3 and cause cell apoptosis (53). Several microRNAs, including miR-21, miR-26a, miR-30, miR-92a, miR-126, miR-139, miR-199a, miR-222, and miR-let7d, regulate vascular homeostasis.…”
Section: Effects Of T2dm On the Circulatory Systemmentioning
confidence: 99%
“…The expressions of MV markers (CD63 and CD9) were detected, and the results showed that the isolation was successful ( Figure 1B). Meanwhile, miRNAs including let-7a-5p, 28 miR-103a-3p, 29 miR-191-5p, 30 and miR-26a-5p 31 have been reported to be related to cell apoptosis, proliferation, migration, and angiogenesis of HUVECs. Therefore, the expressions of let-7a-5p, miR-103a-3p, miR-191-5p, miR-377, and miR-26a-5p were compared in CC-MVs with or without interfering E6/E7.…”
Section: Mir-377 Was Increased In E6/ E7-interfering Cc-mvsmentioning
confidence: 99%
“…The pelleted EMPs were re-suspended in endothelial cell medium at a concentration of 1.0 × 10 7 MP/ml. HUVECs seeded on 6-well plates were treated with an equal number of EMPs (50 μl)[ 20 ] for 24 h under normoxic condition. Finally, HUVECs were used for migration and tube formation assays or were collected for real-time polymerase chain reaction (RT-PCR) and quantitative protein assay.…”
Section: Ethodsmentioning
confidence: 99%